An overview on rare earth management in Malaysia - Abd Hamid, Khairul Bariyah; Abu Samah, Mohd Armi; Yunus, Kamaruzzaman; Abdullah Suhaimi, Afiza (Penerbit Universiti Malaysia Pahang, 2016)
The demand for rare earth elements (REEs) are rapidly increasing each year. The estimated world demand for rare earth elements is 136,000 metric tons per year. This demand is projected to rise to 185,000 metric tons annually by 2015. Currently, China is the global supply of the REEs. To overcome this problem, Malaysia has become one of the countries that provide rare earth production (separation and refining). One of the REEs industries in Malaysia was located in Pahang. Although relatively abundant in the earth’s crust, the REEs rarely occur in concentrated forms, making them economically challenging to obtain. These elements constitute critical components of many important technologies and products, such as hybrid vehicles, wind turbines, and cell phones. The REEs are a group of 15 chemical elements in the periodic table. The REEs are all metals, and the group is often referred to as the “rare earth metals”. The REEs need to be properly managed. Thus, this paper will discuss about management on the resources, the process (application), and the disposal of REEs in the industry. As a nation, Malaysia will significantly benefit from the contribution of rare earths by become the foundation industry for other high- technology industries that use rare earth and also can contribute and support the development of a green economy both domestically and globally.